2016
DOI: 10.22159/ijpps.2017v9i1.14635
|View full text |Cite
|
Sign up to set email alerts
|

Novel Umbelliferone Phytosomes: Development and Optimization Using Experimental Design Approach and Evaluation of Photo-Protective and Antioxidant Activity

Abstract: <p><strong>Objective: </strong>The objective of this study was to develop a novel formulation (Phytosome) of umbelliferone with phospholipid for improved permeability, solubility and hence better pharmacological action.</p><p><strong>Methods: </strong>The phytosomal complex was prepared by using solvent evaporation method and optimised by applying the Box-Behnken design on the basis of complexation rate and partition coefficient. The formation of phytosomes was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…These results suggest that the RNPs are more permeable than free rutin (p < .05), across both the skin specimens. Our results are in good agreement with previous studies reported with phospholipid complex of sinigrin [57], elagic acid [58], curcumin [59], puerarin [60], oxymatrine [61], lawsone [62], ferrulic acid [63], morin [64] and umbelliferon [65]. Compared to free drug, drug-phospholipid complex enhanced the rate and extent of drug permeation across the biomembrane.…”
Section: Ex Vivo Drug Permeation Studysupporting
confidence: 92%
“…These results suggest that the RNPs are more permeable than free rutin (p < .05), across both the skin specimens. Our results are in good agreement with previous studies reported with phospholipid complex of sinigrin [57], elagic acid [58], curcumin [59], puerarin [60], oxymatrine [61], lawsone [62], ferrulic acid [63], morin [64] and umbelliferon [65]. Compared to free drug, drug-phospholipid complex enhanced the rate and extent of drug permeation across the biomembrane.…”
Section: Ex Vivo Drug Permeation Studysupporting
confidence: 92%
“…FTIR analysis was performed on powders (Figure 2A), monolayer (Figure 2B), and bilayer films (Figure 2C) in order to identify the influence of the additives on the chemical structure of the PLA. The FT-IR spectrum of umbelliferone showed a sharp peak of OH group at 3,153 cm −1 (Ittadwar and Puranik, 2017), frequencies identified at 3,122 and 2,987 cm −1 are designated to C-H stretching vibrations, single bonded carbonyl group vibrations at 1388, 1,345, and 1,233 cm −1 , while frequencies at 1,578, 1,454, 1,446, 1,409, and 1,386 cm −1 have been designated to C-C stretching vibrations (Rexali, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of Phospholipon 90H gave characteristic C-H stretching band of long chain fatty acid at 2916.37 cm -1 and 2848.86 cm -1 [28]. Also, a C=O band at 1467.83 cm -1 ; a − a (so3)3 band at 923.90 cm -1 and a P-O-C stretch at 968.27 cm -1 [29].…”
Section: Characterization Of Optimized Cga Phytovesicles Ftir Spectroscopymentioning
confidence: 96%